2013
DOI: 10.1111/ijal.12029
|View full text |Cite
|
Sign up to set email alerts
|

Variable beliefs about the need for accuracy in the oral production of German: an exploratory study

Abstract: This study explores how learner variables interact with beliefs about the need for morphosyntactic, lexical, phonological, and pragmatic accuracy in oral foreign language production for four purposes: comprehensibility and pleasantness (respectively) to native speakers (NSs), a course grade of A, and a sense of personal accomplishment. Three-hundred-and-forty-nine first-, second-, and third-year American college learners of German rated 19 items representing different features of German on four 5-point Likert … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…errors in word order, missing elements), phonology (e.g. pronunciation, stress and intonation), and pragmatics (Chavez, 2014; Rezaee et al, 2019). In terms of the conceptualization of fluency, Segalowitz (2010) proposed that from a research perspective, fluency was three‐dimensional, including cognitive fluency, utterance fluency and perceived fluency.…”
Section: Related Workmentioning
confidence: 99%
“…errors in word order, missing elements), phonology (e.g. pronunciation, stress and intonation), and pragmatics (Chavez, 2014; Rezaee et al, 2019). In terms of the conceptualization of fluency, Segalowitz (2010) proposed that from a research perspective, fluency was three‐dimensional, including cognitive fluency, utterance fluency and perceived fluency.…”
Section: Related Workmentioning
confidence: 99%
“…Recent research data indicate that female learners tend to score higher than male learners on different measures of language achievement, such as accuracy in oral production (Chavez, ), general English proficiency test (Główka, ), judgements of accents in terms of likeness to native speakers (Polat, ), lexical availability (Fernandez Fontecha, ), and vocabulary production tests (Jimenez Catalan, ). Further, Chavez's () review of studies looking at gender and achievement confirmed that females outperformed males in placement tests and were graded more highly, although she also concluded that “as far as assessments in experimental settings are concerned, the female advantage is much less clear” (Chavez, : 67).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies on differences in motivation to learn foreign languages have shown stronger motivation among female than male learners. A slightly higher level of motivation among girls than boys has been established by research in different countries, including Canada (Kissau, 2006;Kissau et al, 2010), China (Ahåt, 2013), the United Kingdom (Williams et al, 2002), Hungary (Dörnyei et al, 2006), Korea (Kim & Kim, 2011), Poland (Okuniewska et al, 2010), Sweden (Henry, 2009), Turkey (Öztürk & Gürbüz, 2013;Polat, 2011) and the United States (Brantmeier et al, 2013;Chavez, 2014). Males were less motivated than females when learning various languages, for example English (Dörnyei et al, 2006;Henry, 2009;Kim & Kim, 2011;Ahåt, 2013;Öztürk & Gürbüz, 2013), French (Williams et al, 2002, Kissau, 2006Dörnyei et al, 2006), German (Williams et al, 2002, Dörnyei et al, 2006Chavez, 2014), Hebrew (Okuniewska et al, 2010), Italian (Dörnyei et al, 2006), Kurdish (Polat, 2011), Russian (Dörnyei et al, 2006) and Spanish (Kissau et al, 2010;Brantmeier et al, 2013).…”
mentioning
confidence: 97%